2007
DOI: 10.1177/0363546507309672
|View full text |Cite
|
Sign up to set email alerts
|

The J-Bone Graft for Anatomical Glenoid Reconstruction in Recurrent Posttraumatic Anterior Shoulder Dislocation

Abstract: The J-bone graft is capable of creating a stable shoulder joint without causing extensive loss of motion on the long term in patients with traumatic glenoid rim fractures after shoulder dislocation. In some patients, mild to moderate arthropathy develops despite anatomical glenoid reconstruction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
170
0
13

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 159 publications
(185 citation statements)
references
References 36 publications
2
170
0
13
Order By: Relevance
“…Studies have reported good outcomes in the use of iliac crest bone autograft in patients. However these studies are limited by small population groups and limited followup period [67][68][69] . The use of a distal clavicle arthroscopic autograft has also been reported [70] .…”
Section: Glenoid Bone Lossmentioning
confidence: 99%
“…Studies have reported good outcomes in the use of iliac crest bone autograft in patients. However these studies are limited by small population groups and limited followup period [67][68][69] . The use of a distal clavicle arthroscopic autograft has also been reported [70] .…”
Section: Glenoid Bone Lossmentioning
confidence: 99%
“…1,2,10 There are only a few published all-arthroscopic iliac crest graft augmentation techniques, including those of Taverna et al 11 using metal screws and, more recently, EndoButton devices (Smith & Nephew); Scheibel et al 12 with the use of bioabsorbable screws; and Anderl et al 13 with implant-free, Jebone graft reconstruction. 14 We consider our proposed technique to have several advantages (Table 2). Possible risks include malpositioning of the graft; therefore, correct placement of the glenoid guide is important.…”
Section: Discussionmentioning
confidence: 99%
“…In the more recent series, with well-fixed transplants, the recurrence rate is very low [13][14][15]17] Arthritis is seen more often, although mostly mild; reports are not always clear on the prevalence of preoperative arthritis and further deterioration. Development of arthritis is possibly prevented when, after fixing the graft the capsule is reattached on the rim of the native glenoid, thus, placing the bone block extra-articularly [15].…”
Section: Complicationsmentioning
confidence: 96%
“…The technique shows a wide variation: the graft is either fixed by impaction in the scapular neck, the so-called J graft [13]. In most of the other studies the graft is fixed with screws.…”
Section: Glenoid Reconstruction With Autologous Bonementioning
confidence: 99%
See 1 more Smart Citation